Teknologi Tepat Guna Kemudahan Mobilisasi Nelayan Desa Kalembak, Kelurahan Sambau, Kecamatan Nongsa, Kota Batam, Provinsi Kepulauan Riau - Amanda Rosetia; Willy Ivander; Dea Fanny; Emilia Rossalina; Felicia Felicia; Fernando Fernando; Intan Christien; Ivo Valentine; Jessica Jessica; Meriani Meriani; Monica Monica (National Conference for Community Service Project (NaCosPro), 2019)
Kalembak Village located strategically on the shore of the open ocean and has open access to City Center. Marine sources are their common survival method for living. Their fishers are actively growing the family income from fishing such as fish, shells, crabs, and etc. In order for them to get customers are varied. Some of them have the ability to get tied with customers and get them to come by phone to take the morning catch, but not few have to go the extra mile to get a penny from customers. Those who go around are depending on the lucky factors through their not advance facility. Armed with a small plastic bucket to carry the fishes placed in front of their motorcycle, fishers go through the city to find those who willing to buy their catches. The writer sees this phenomenon as a constraint to fishers’ value of income. The ability to catch more than their usual actually obstructed by the fact they can only carry a small amount on a plastic bucket. Through this social empowerment program, the writer has come with the solution idea for the Kalembak fishers in order to ease their mobility service. By doing a purposive sampling on a qualitative method and observation, the writer finds the data on Kalembak fishers who need enhancement on their mobilization. For result, the Kalembak fishers get to multiply and increase their usual catch and income